The Effect of Behavioral Approach Group Counseling Services on the Tendency of Aggressive Behavior of Students of Public Junior High School 48 Surabaya - Erwin Dwiyono; Wangid, Muhammad Nur (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2025)
Behavioral approach group counseling services are counseling services using a behavioral approach that is implemented in a group setting by utilizing group dynamics to alleviate problems experienced by individuals. The implementation process consists of four stages, namely the formation stage which contains introductions to the delivery of goals, principles and with games as intimacy, the transition stage which contains the stabilization of the group members, the activity stage which contains the discussion of problems or topics that occur in the group, and the termination stage which contains the delivery of group counseling results as well as responses and suggestions from group members. As for this study, researchers carried out group counseling treatment 8 times with material, 1) Self- Concept, 2) Emotional Intelligence, 3) Recognizing physical and verbal aggressive behavior, 4) How to Reduce Aggressive behavior. This research method uses quantitative with a sample of 30 students of SMP Negeri 48 Surabaya, with a Likert scale model, the data is collected and processed with non-parametric statistical techniques Willcoxon Signed Rank Test with SPSS. The results of the study through the t test of the measurement scale of students' aggressive behavior using the SPSS program obtained the difference in means (mean) between groups, namely 4.167, standard deviation = 3.667, mean standard error = 0.669, t count = 6.222, degree of freedom (df) = 29 at the chance of error (p) = 0.000 (significant). It turns out that the calculated t number obtained is 6.222 at an error chance (p) = 0.000 which is smaller than the error chance (p) = 0.05, or 0.000 <0.05 which means significant.